Short term effects of antenatal maternal betamethasone administration on CTG - T., Jayanthy; Raman, Ragvi; Anjanappa, Sanvithi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Antenatal administration of corticosteroids to pregnant women has proven to enhance lung maturation, prevent respiratory distress syndrome and provide neuroprotection to the foetus. When betamethasone is given antenatally, it has been observed to transiently reduce fetal movements and fetal heart rate variability; which are often used as indicators of fetal wellbeing. Aim and objectives of the present study was planned to assess the short-term effects of antenatal betamethasone administration on fetal heart rate and its variability by visual interpretation of CTG Methods: A total of 30 women between gestational age of 28 weeks to 36 weeks 6 days with singleton pregnancy requiring maternal betamethasone administration were enrolled and the first CTG was taken. First dose of injection betamethasone 12 mg i.v. was administered and second CTG was taken 6 hours later and both the CTGs were compared. Results: After 1st dose of antenatal betamethasone, 90% of the cases had changes in fetal heart rate on CTG. In 53.3% cases, the baseline fetal heart rate was reduced while in 46.7% there was no change. There was reduced fetal heart rate variability in 56.7% cases while 23.3% cases had increased variability and rest 20% had no observable change. 73.3% study patients delivered and 26.6% study patients continued pregnancy. Among those who delivered, 20% neonates required neonatal ventilator support and 10% required oxygen support. All neonates were eventually discharged. Conclusions: Maternal betamethasone administration can cause changes in fetal heart rate and variability on CTG. Hence, other fetal parameters have to be considered before concluding fetal distress as these changes maybe transient. In our study, though CTG changes were seen in 90% cases, only 20% cases required neonatal ventilator support.